POTENSI KAVAIN DALAM PIPER METHYSTICUM SEBAGAI TATALAKSANA PREVENTIF GENERALIZED ANXIETY DISORDER - Devin Mahendika (Kelompok Ilmiah Hippocrates Fakultas Kedokteran Universitas Udayana, 2022)
Introduction: Generalized Anxiety Disorder (GAD) was a psychiatric disorder characterized by anxiety, motor tension, and autonomic overactivity. Piper methysticum was a plant that had efficacy in various therapies including GAD because of its chemical substance cavaine. Cavaine was a biological ingredient in Piper methysticum which had potent anxiolytic activity. Piper methysticum extract can be used as a preventive therapy for GAD due to its anxiolytic effect on the symptoms of GAD. Discussion: Piper methysticum in its efficacy was able to potentiate GABAARs without subtype selectivity, besides that the concentration of GABA responds to the performance of 4?2? GABAARs significantly, so that the performance of cavaine works effectively and sensitively in the target system in addition to the 1?2?2L receptor. Cavaine also showed a modest increase in GABA concentrations below EC45, but it did not affect EC50 and maximal efficacy of GABA. In addition, the chalcone synthase chain which is broken due to neurodegeneration by the RpBASi enzyme which can extend a single polypeptide chain can be repaired by cavaine. Another effect of cavaine was that it can modulate volt-gated calcium and sodium channels and antagonize Ca2+ channels. Another important activity of cavaine was being able to bind to GABA receptors in the central nervous system besides functioning as an anxiolytic in the serotonergic and glutamanergic pathways. Piper methysticum in its properties is able to potentiate GABAARs without subtype selectivity, besides that the concentration of GABA responds to the performance of 4?2? GABAARs significantly, so that the performance of cavaine works effectively and sensitively in the target system in addition to the 1?2?2L receptor. Cavaine also showed a modest increase in GABA concentrations below EC45, but it did not affect EC50 and maximal efficacy of GABA. In addition, the chalcone synthase chain which was broken due to neurodegeneration by the RpBASi enzyme which can extend a single polypeptide chain can be repaired by cavaine. Another effect of cavaine, that it was able to modulate volt-gated calcium and sodium channels and acts as an antagonist to Ca2+ channels. Another important activity of cavaine was its ability to bind to GABA receptors in the central nervous system in addition to functioning as anxiolytics in serotonergic and glutamanergic pathways. Conclusion: The use of Piper methysticum as an effort to prevent GAD has proven to be superior because it was cheap and easy to obtain, had no side effects, and had high effectiveness in reducing GAD in accordance with its effects and clinical features. Therefore, further research on clinical trials of the use of Piper methysticum continues to be developed so that it can be implemented ethically to prevent GAD. Keywords: Piper methysticum, cavaine, GAD